Inovasi Pembelajaran di PTAI (Analisis Kebutuhan Penerapan Model Pembelajaran Research-based Learning) - Hajriana Hajriana (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
Being a university that implements research-based education is one of the missions of Islamic Religious Education study program at PTAI East Kalimantan. It will be difficult to realize if students have lack abilities to do research. This study aims to analyze the importance of learning inovations by applying research-based learning and student characteristic of PAI study program by qualitative method. The results showed that implementation of learning in Islamic Religious Education study program at PTAI did not support the improvement of student research abilities, so it needed to be supported through learning innovations that were integrated research activities in the form development and application of research-based learning that was adjusted to the characteristics of the learners were millennial and part-time students.